Teaching companies how to be entrepreneurial: cultural change at all levels. Issue 2 (30th October 2018) - Gillin, Laurence Murray; Gagliardi, Rebecca; Hougaz, Laura; Knowles, David; Langhammer, Michael
Abstract : Purpose: This case study aims to show how a strategic intervention, using an in-house delivered university entrepreneurship education program, cultivates an entrepreneurial mindset and effective innovation culture amongst company staff. The intervention produces a measured change in staff decision making style from analytical to a more intuitive style. Also assessed is the resulting management-style change to the firm's internal environment, strategic motivation and performance. Design/methodology/approach: Through a qualitative longitudinal study of Partners and staff in the firm, the authors measure the impact of the selection, integration and performance of in-house entrepreneurship education on firm culture. Findings: The authors identify organisation factors that inhibit staff entrepreneurial behaviour and by integrating an in-house education intervention, demonstrate unambiguously the resultant effective culture and entrepreneurial mindset. Research limitations/implications: Generalising results from this single longitudinal case study requires caution. The positive outcome from the in-house education concept can be considered for further evaluation within other organisations. Practical implications: Using an entrepreneurial health-audit to assess in-firm cultural behaviour enables management to identify factors fostering/inhibiting entrepreneurial activity and devise interventions to cultivate a firm-wide entrepreneurial mindset. Originality/value: In-house education is not a new concept, but a targeted focus on entrepreneurship applied strategically to a committed firm shows outstanding results. The added-value is in the demonstrated enhancement to effective innovation outcomes.